2013
DOI: 10.1111/dme.12047
|View full text |Cite
|
Sign up to set email alerts
|

External validity of randomized controlled trials of glycaemic control and vascular disease: how representative are participants?

Abstract: Aims To describe the proportion of people with Type 2 diabetes living in Scotland who meet eligibility criteria for inclusion in several large randomized controlled trials of glycaemic control to inform physicians and guideline developers about the generalizibility of trial results.Methods A literature review was performed to identify large trials assessing the impact of glycaemic control on risk of macrovascular disease. Inclusion and exclusion criteria from each trial were applied to data on the population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 28 publications
3
88
0
3
Order By: Relevance
“…Conclusions Our findings from this inclusive populationlevel investigation confirm and expand on trial evidence from more selected populations [34,35], concerning the management of HbA 1c and BP but not total cholesterol. Further corroboration is necessary, particularly in prospective longitudinal trials but, if validated, the findings have several implications for type 2 diabetes management.…”
Section: Discussionsupporting
confidence: 81%
“…Conclusions Our findings from this inclusive populationlevel investigation confirm and expand on trial evidence from more selected populations [34,35], concerning the management of HbA 1c and BP but not total cholesterol. Further corroboration is necessary, particularly in prospective longitudinal trials but, if validated, the findings have several implications for type 2 diabetes management.…”
Section: Discussionsupporting
confidence: 81%
“…That is, they would have to modify the relative or absolute treatment effects of statins on CVD as they are translated to real-world settings from the trials 15. The proportions of patients deemed eligible in our study were similar to those recently reported in the UK for RCTs on novel oral anticoagulants (48–64%)34 and for the UK Prospective Diabetes Study (32–51%)35 but clearly higher than those for various other RCTs on intensive glucose lowering (4–36%) 35. The background risk, reflected in the cumulative risk for CVD events after statin initiation among patients deemed ineligible, was either similar or remarkably higher as compared with those eligible.…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, older patients are often underrepresented in large clinical trials; therefore, data on antihyperglycemic medications are often extrapolated from younger populations (72).…”
Section: Medications In the Management Of Hyperglycemiamentioning
confidence: 99%